2011
DOI: 10.1371/journal.pone.0023321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bacterial Communities in a Potato Field as Determined by Pyrosequencing

Abstract: BackgroundPlants selectively attract particular soil microorganisms, in particular consumers of root-excreted compounds. It is unclear to what extent cultivar type and/or growth stage affect this process.Methodology/Principal FindingsDNA-based pyrosequencing was used to characterize the structure of bacterial communities in a field cropped with potato. The rhizospheres of six cultivars denoted Aveka, Aventra, Karnico, Modena, Premiere and Desiree, at three growth stages (young, flowering and senescence) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
117
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(132 citation statements)
references
References 54 publications
13
117
2
Order By: Relevance
“…Although these are interesting results, it should be noted that the abundance of seed transmitted bacteria we have observed in these juvenile rhizospheres may be exaggerated because they have not yet had a chance to be more heavily colonized during passage through soil as would older and larger root systems (Inceoglu et al 2011). As plants age, their rhizosecretions also change which can alter the microbial populations living around the root (Chaparro et al 2014).…”
Section: Discussionmentioning
confidence: 79%
“…Although these are interesting results, it should be noted that the abundance of seed transmitted bacteria we have observed in these juvenile rhizospheres may be exaggerated because they have not yet had a chance to be more heavily colonized during passage through soil as would older and larger root systems (Inceoglu et al 2011). As plants age, their rhizosecretions also change which can alter the microbial populations living around the root (Chaparro et al 2014).…”
Section: Discussionmentioning
confidence: 79%
“…This indicates that the DNA extraction procedure introduces significant bias, thereby influencing the interpretation of the microbial community observed. PCR-based metagenomic approaches such as DGGE Ramond et al, 2013), t-RFLP (Sessitsch et al, 2012;Ding et al, 2013) and next generation sequencing (Gottel et al, 2011;Lucero et al, 2011;Ìnceoğlu et al, 2011;Molina et al, 2012) are continuously used to elucidate the structure and ecological roles of plant-associated (and other) microbial communities. However, few, if any, of these studies share the same DNA extraction protocol and/or are preceded by an evaluation of DNA extraction procedures to select the most efficient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Micallef et al (2009a) through denaturing gradient gel electrophoresis analysis observed that Arabidopsis rhizosphere microbial communities varied with plant development and that microbial communities in early plant development were more distinct to the bulk soil and that this difference decreased with plant age. Similarly, an assessment of the potato rhizosphere demonstrated that young potato plants showed cultivar-dependent rhizosphere microbial communities but these differences in the microbiomes disappeared as the plants aged (Inceoglu et al, 2011). Soybean rhizosphere microbial communities were also influenced by plant development; early reproductive growth stages of the soybean plant produced more complex microbial communities than late stage soybean plants (Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%